YOUTH PERCEPTIONS TOWARDS ENTREPRENEURSHIP IN SOUTH AFRICA - Elvis Madondo; Faith Tinonetsana (Baltic Journal of Economic Studies)
In South Africa, the field of youth entrepreneurship is confronted with considerable obstacles, many of which are rooted in the country's historical economic inequalities, which were further exacerbated by the apartheid era. This study aims to gain insight into the perceptions of youth regarding entrepreneurship by employing the Entrepreneurial Event Theory (EET) to analyse these perceptions through the lenses of desirability, feasibility, and propensity to act. EET was used to provide a structured understanding of how attitudes towards entrepreneurship, perceived capability and propensity to act influence entrepreneurial engagement. The thematic analysis of qualitative data from semi-structured interviews revealed that while South African youth have a strong desire to use entrepreneurship to address unemployment and economic inequality, their active engagement is limited. Participants expressed high aspirations for entrepreneurship due to its potential for financial independence and personal fulfilment. Nevertheless, this enthusiasm is tempered by perceived feasibility concerns, including challenges related to financial resources, regulatory complexities, and intense market competition. Moreover, the propensity to act varies; some young people demonstrate a proactive attitude, while others are hesitant due to perceived risks and systemic barriers. The study recommends integrating comprehensive entrepreneurship education across all educational levels, launching national and community-level campaigns to promote an entrepreneurial culture and showcase success stories, and advocating for policies to enhance access to funding. These measures aim to improve the overall feasibility and increase the propensity to act among South African youth, thereby fostering a more vibrant entrepreneurial landscape.